Порядок формування, структура та повноваження двопалатного парламенту в Україні - Ковальчук, Олена; Kovalchuk, Olena; Ковальчук, Елена (Видавництво Львівської політехніки, 2017)
Дослідження присвячено розглядові проблемних питань запровадження двопалатного парламенту в Україні. Запропоновано формувати Верховну Раду України з двох палат: нижньої – Палати представників і верхньої – Палати регіонів, щоб нижня Палата складалася зі 189 депутатів, верхня з 27 депутатів. Загалом парламент налічував би 216 депутатів. Депутатом нижньої палати може бути громадянин України, який на день виборів досяг 35 років, верхньої – 40 років, та повинні проживати в Україні останні десять років. Нижню – Палату представників формувати на основі пропорційної системи. Для проведення голосування утворювати 27 багатомандатних округів і від кожного округу обирати по 7 депутатів. Вибори проводити за відкритими партійними списками, а виборчу квоту визначати окремо в кожному виборчому окрузі. Для розподілу мандатів між партіями – кількість голосів виборців за кожну окрему партію, що подолала 10 % бар’єр ділити на виборчу квоту. Верхню – Палату регіонів формувати виключно з голів обласних рад, яких обирати не депутатами відповідної ради, а громадянами відповідної територіальної громади за мажоритарною системою відносної більшості.

The research is devoted to the consideration of problematic issues of the introduction of a bicameral parliament in Ukraine. It is proposed to form the Verkhovna Rada of Ukraine from two chambers: the lower one – the House of Representatives and the upper – the Chamber of Regions, so that the lower chamber consisted of 189 deputies, and the upper chamber – 27 deputies. In total, the parliament would have 216 deputies. A lower house’s deputy may be a citizen of Ukraine, who on the day of elections has reached 35 years of age, the upper one is 40 years old and must have lived in Ukraine for the last ten years. Lower – the House of Representatives to form on the basis of a proportional system. For voting, to form 27 multi-mandate constituencies and to elect seven deputies from each district. Elections to be held on open party lists, and the election quota should be determined separately in each constituency. For distribution of mandates between parties – the number of votes for each individual party that has exceeded 10% barriers to divide the election quota. Upper – the Chamber of Regions to form solely from the heads of regional councils, which are not elected by deputies of the relevant council, but by the citizens of the respective territorial community according to the majority system of the relative majority.

Исследование посвящено рассмотрению проблемных вопросов введения двухпалатного парламента в Украине. Предлагается формировать Верховную Раду Украины с двух палат: нижней – Палаты представителей и верхней – Палаты регионов, чтобы нижняя палата состояла из – 189 депутатов, верхняя из – 27 депутатов. В общем парламент насчитывал бы – 216 депутатов. Депутатом нижней палаты может быть гражданин Украины, достигший на день выборов 35 лет, верхней – 40 лет, и должны проживать в Украине последние десять лет. Нижнюю – Палату представителей формировать на основе пропорциональной системы. Для проведения голосования образовывать 27 многомандатных округов и от каждого округа избирать по 7 депутатов. Выборы проводить по открытым партийным спискам, а избирательную квоту определять отдельно в каждом избирательном округе. Для распределения мандатов между партиями – количество голосов избирателей за каждую отдельную партию, которая преодолела 10% барьер делить на избирательную квоту. Верхнюю – Палату регионов формировать исключительно из председателей областных советов, которых избирать не депутатами соответствующего совета, а гражданами соответствующей территориальной общины по мажоритарной системе относительного большинства.
Order of formation, structure and authority of the two parliament in Ukraine
Порядок формирования, структура и полномочия двухпалатного парламента в Украине
Keywords: двопалатний парламент; структура парламенту; повноваження парламенту; закон; палати парламенту; депутати; голова обласної ради; вибори; bicameral parliament; parliament structure; powers of the parliament; law; parliamentary chamber; deputies; chairman of the regional council; elections; двухпалатный парламент; структура парламента; полномочия парламента; закон; палаты парламента; депутаты; председатель областного совета; выборы; 342.533